The Effect of Jigsaw towards Third Year Studentsâ€™ Learning Interest in IAIN Bukittinggi - Hasnawati, Hasnawati (AT-TA'LIM, 2016)
This research aims to determine: 1). The implementation of Jigsaw in test and Â evaluation course for third semester students of Islamic education department in IAIN Bukittinggi; 2). The types of studentsâ€™ learning interest in test and evaluation course; and 3). The effect of Jigsaw towards studentsâ€™ learning interest at Islamic education department in IAIN Bukittinggi. This research was conducted through survey method using regression analysis with one predictor. The total population in this research is 353 students in which 11.9% of them is taken as sample (42 students). The data were collected through questionnaire, documentation, and observation. The findings of the study showed that: 1). Jigsaw is in the â€œaverageâ€ category with the mean score 66 in 65-67 interval; 2). Third semester studentsâ€™ learning interest of Islamic education department in IAIN Bukittinggi is in â€œaverageâ€ category with the mean score of 65.95 in 65-67 interval; and 3). There is a positive effect of Jigsaw towards learning interest in test and evaluation course for third semester students of Islamic education department in IAIN Bukittinggi, which is demonstrated from the statistical analysis rxy= 0.6365 while from hypothesis testing by simple regression analysis, it is obtained that Y = 0.5182 X + 31.3701. it is concluded that there is significant effect of Jigsaw towards studentsâ€™ learning interest in test and evaluation course for third semester students of Islamic education major in IAIN Bukittinggi.